Effectiveness of pneumococcal Haemophilus influenzae protein D conjugate vaccine against pneumonia in children: A cluster-randomised trial. Issue 39 (18th September 2018) - Kilpi, T.M.; Jokinen, J.; Puumalainen, T.; Nieminen, H.; Ruokokoski, E.; Rinta-Kokko, H.; Traskine, M.; Lommel, P.; Moreira, M.; Ruiz-Guinazu, J.; Borys, D.; Schuerman, L.; et al.
Highlights: First European trial on effectiveness of a PCV against pneumonia in children. PHiD-CV10 reduced any hospital-diagnosed pneumonia by 27%. Reduction of pneumonia with alveolar consolidation or pleural effusion by 45%. Vaccine-preventable incidence of pneumonia considerable for a high-income setting. We used vaccine as a probe to estimate disease burden. Abstract: Background: Pneumococcal conjugate vaccines have potential to prevent significant proportion of childhood pneumonia. Finnish Invasive Pneumococcal disease vaccine trial was designed to assess the vaccine effectiveness (VE) of the 10-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10) against several outcomes. We now report results for pneumonia. Methods: In this nationwide, cluster-randomised, double-blind trial, children younger than 19 months received PHiD-CV10 in 52 clusters or hepatitis vaccines as control in 26 clusters. Infants younger than 7 months at the first vaccination received either 3+1 or 2+1 vaccination schedule, children aged 7–11 months received 2+1, and those 12–18 months of age two-dose schedule. All hospitalizations and outpatient visits to hospital associated with ICD-10 codes compatible with pneumonia were identified through the National Care Register and 1–3 frontal chest X-ray images per event were collected. External readers who were unaware of the patients' vaccination status retrospectively interpreted the images. The evaluated outcomes were hospital-diagnosed, hospital-treated pneumonia as primary diagnosis, and radiologically confirmed pneumonia during the blinded, intention-to-treat follow-up period from the first vaccination to the end of 2011. Total VE was calculated as 1 minus rate ratio of all pneumonia episodes. Results: 47 366 children were enrolled from February 2009, to October 2010. VE against all episodes of hospital-diagnosed pneumonia was 27% (95% confidence interval [CI]: 14%, 38%), 32% (95% CI: 3%, 52%), and 23% (95% CI: −5%, 44%) in subjects enrolled at age <7, 7–11, and 12–18 months, respectively. Corresponding rate reductions were 3.4, 4.7, and 2.5 per 1000 person-years. VE estimates against pneumonia with alveolar consolidation or pleural effusion (WHO criteria) in the three cohorts were 45% (95% CI: 26%, 60%), 56% (95% CI: 14%, 77%), and 48% (95% CI: 2%, 73%), respectively. Conclusion: PHiD-CV10 vaccination remarkably reduced disease burden due to pneumonia in infants and young children. Clinical trial registration: Main trial NCT00861380, nested carriage and otitis media trial NCT00839254 (ClinicalTrials.gov ).